Resource rents, power, and political stability - Kjetil Bjorvatn; Mohammad Reza Farzanegan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
We study the association between resource rents and political stability, highlighting the importance of the distribution of political power as a mediating factor. We present a simple theoretical model showing that increased rents are likely to be positively associated with the stability of a powerful incumbent while destabilizing a less powerful incumbent. Our empirical analysis confirms this prediction: Using panel data for more than 120 countries from 1984-2009, our results show that rents can promote political stability, but only when the political power is sufficiently concentrated. Indeed, if the incumbent is sufficiently weak, rents fuel instability. Our main results hold when we control for the effects of income, quality of institutions, time varying common shocks, country fixed effects and various additional covariates.
Keywords: 330; resource rent; political power; political stability; conflict